АДАПТАЦІЯ УКРАЇНСЬКОГО БІЗНЕСУ ДО СУЧАСНИХ ВИКЛИКІВ ТА ЗАГРОЗ - Терлецька, Юлія (Modern aspects of the modernization of science: state, problems, development trends, 2026)
In the face of modern challenges and threats, top managers of business entities are forced to continuously adapt to permanent changes in the operating environment. At the same time, representatives of Ukrainian business pay special attention to the need for systematic improvement of existing forms and methods in order to ensure their own livelihood. Today, the problems of adapting enterprises to new conditions by making the necessary changes to management systems, which are the basis of their effective activities and without which not only functioning and development, but also further existence, are becoming particularly relevant. Given this fact, the process of adapting Ukrainian business to changes should be directed not at solving existing problems, but at the practical implementation of promising opportunities at the expense of existing market advantages.
ADAPTATION OF UKRAINIAN BUSINESS TO CURRENT CHALLENGES AND THREATS